Radiation shielding of upgraded accelerator LUE-10M - Mitrochenko, V.V.; Pugachev, G.D.; Uvarov, V.L.; Repikhov, O.A.; Tenishev, A.Eh.; Shestakova, V.S. (Вопросы атомной науки и техники, 2018)
The LUE-10M accelerator operating in NSC KIPT is used for sterilization of a considerable amount of medical
products in Ukraine, thereby contributing to national security and health of population. However, by the present
time the accelerator component parts have become worn out and outdated. So, it is anticipated that the LUE-10M
should be upgraded on the basis of new hardware components with arrangement in the same premises of a new
10 MeV radiator with average beam current up to 2 mA. The calculations performed have demonstrated that the
characteristics of the actual LUE-10M shield and ventilation systems meet the requirements of the guidelines provided that the accelerator is operated at the design parameters of the beam. На діючому в ННЦ ХФТІ прискорювачі ЛУЕ-10M проводиться стерилізація значного об'єму виробів медичного призначення в Україні і тим самим забезпечується внесок у національну безпеку. До теперішнього
часу комплектуючі вироби прискорювача вичерпали свій ресурс і застаріли. Тому передбачається провести
реконструкцію ЛУЕ-10M на новій елементній базі з розміщенням нового випромінювача з енергією електронів 10 МеВ і середнім струмом пучка до 2 мА в тому ж приміщенні. Проведені розрахунки показують, що
при роботі прискорювача з проектними параметрами пучка характеристики наявного радіаційного захисту і
системи вентиляції ЛУЕ-10M задовольняють вимогам нормативних документів. На действующем в ННЦ ХФТИ ускорителе ЛУЭ-10M производится стерилизация значительного объема
изделий медицинского назначения в Украине и тем самым обеспечивается вклад в национальную безопасность. К настоящему времени комплектующие изделия ускорителя выработали свой ресурс и устарели, поэтому предполагается провести реконструкцию ЛУЭ-10M на новой элементной базе с размещением нового
излучателя с энергией 10 МэВ и средним током до 2 мА в том же помещении. Проведенные расчеты показывают, что характеристики имеющейся защиты и системы вентиляции ЛУЭ-10M при работе ускорителя с
проектными параметрами пучка удовлетворяют требованиям нормативных документов.